Breakdown of gliadin peptides by intestinal brush borders from coeliac patients. Issue 9 (September 1984) - Bruce, G; Woodley, J F; Swan, C H
Abstract : The 'missing peptidase' hypothesis to explain the aetiology of coeliac disease has never been satisfactorily resolved and recent reports suggest that coeliac brush borders may have depressed levels of specific peptidase enzymes. It has been inferred from these studies that the subsequent brush border digestion of gliadin peptides may therefore be defective. In this present study a sensitive fluorometric assay was used to measure the hydrolysis of a peptic-tryptic digest of gliadin by both normal and coeliac brush borders. The coeliac brush borders were as efficient as the normals in hydrolysing gliadin peptides and showed no depression of any specific peptidase activity.